2004
DOI: 10.1002/ana.20065
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor mediates vasogenic edema in acute lead encephalopathy

Abstract: Brain injury from inorganic Pb(2+) is considered the most important environmental childhood health hazard worldwide. The microvasculature of the developing brain is uniquely susceptible to high level Pb(2+) toxicity (ie, Pb(2+) encephalopathy) characterized by cerebellar hemorrhage, increased blood-brain barrier permeability, and vasogenic edema. However, the specific molecular mediators of Pb(2+) encephalopathy have been elusive. We found that Pb(2+) induces vascular endothelial growth factor/vascular permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Given the highly angiogenic nature of the VEGF-producing U87MG tumor and the effects of CEP-7055 on reducing tumor microvessel density, the observed reductions in edematous lesions observed in intracranial tumors with CEP-7055 administration alone and in combination with temozolomide are a reasonable experimental outcome in these studies. Similar observations for a reduction in VEGF-mediated cerebral edema have been observed with other VEGFR kinase inhibitors chemically related to CEP-7055 (42).…”
Section: Discussionsupporting
confidence: 84%
“…Given the highly angiogenic nature of the VEGF-producing U87MG tumor and the effects of CEP-7055 on reducing tumor microvessel density, the observed reductions in edematous lesions observed in intracranial tumors with CEP-7055 administration alone and in combination with temozolomide are a reasonable experimental outcome in these studies. Similar observations for a reduction in VEGF-mediated cerebral edema have been observed with other VEGFR kinase inhibitors chemically related to CEP-7055 (42).…”
Section: Discussionsupporting
confidence: 84%
“…Unhealthy, ballooned mitochondria, together with rarified matrices and ill-identified cristae, were observed in the cytoplasm of the Purkinje cells; these findings have already been described in hippocampal neurons in lead-treated rats [52]. It has been suggested that the principal influence of lead acetate on the cerebellum is the suppression of mitochondrial oxidative activity [24].…”
Section: Discussionmentioning
confidence: 74%
“…For example, TNF-α activates Fyn during sepsis, which results in the opening of the AJ, contributing to multiorgan failure, 17 and when P120-catenin mismanages the turnover of VE-cadherin, the permeability required for some kinds of tumor metastasis can occur. 32 VEGF signaling and Src kinase activation are also involved in many disease processes involving AJ disruption and inappropriate permeability, such as lead poisoning 15 and myocardial infarction. 15,33 It has also been shown that patients with dengue hemorrhagic fever have higher serum levels of VEGF and that Andes hantavirus-induced endothelial permeability is related to VEGFR2 signaling by Src; it can be decreased through Src and VEGFR2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…32 VEGF signaling and Src kinase activation are also involved in many disease processes involving AJ disruption and inappropriate permeability, such as lead poisoning 15 and myocardial infarction. 15,33 It has also been shown that patients with dengue hemorrhagic fever have higher serum levels of VEGF and that Andes hantavirus-induced endothelial permeability is related to VEGFR2 signaling by Src; it can be decreased through Src and VEGFR2 inhibitors. [34][35][36] However, we found no evidence in our JUNV model that disruption of AJs is through VEGFR2/Src-mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation